Business information systems technology, development and management for the e-business - Bocij, Paul; Greasley, Andrew; Hickie, Simon (Always learning, 2015)
Business Information Systems does not assume any prior knowledge of IS or ICT, and new concepts are simply defined. New business examples, case studies and web links are fully integrated throughout, illustrating the relevance and impact of information systems in today's business environment. In addition there are a wealth of questions and exercises both in the book and online at www.pearsoned.co.uk/bis enabling students to test their understanding of key topics and issues. This book is ideal for students on any courses related to business information systems or management information systems at undergraduate or postgraduate level.